(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: Epidemiological observations have shown that the consumption of high-fat diets has increased dramatically across the globe and is the root cause of metabolic diseases including obesity, diabetes, and cardiovascular diseases. Such diets are also associated with renal pathology leading to structural and functional alterations of the kidneys and may result in the development of chronic renal disease and other related disorders. Objective: To observe the effects of a high-fat diet on the renal structure and analyze the histomorphometric findings of renal tissues of male albino rats. Study Design: A cross-sectional experimental study. Place and Duration of Study: This study was conducted at the Department of Anatomy, Peshawar Medical College Peshawar from 05-July 2020 to 05-Oct 2020. Methods: The present study is a cross-sectional experimental study. which was carried out with 20 rats in the Department of Anatomy, Peshawar Medical College Peshawar Structural changes and assessment of the morphometric renal parameters were made using light microscopy. Results: This study includes a total number of 20 male adult albino rats that were classified equally and randomly into two groups as follows; the Control group where rats were administered the control diet, and the experimental group fed on high-fat diet HFD (30%) for 3 months. At the end of the experiment, Kidney samples were examined histologically. The body mass indices of the control and experimental groups were 4.528 ± 0.242 and 5.876 ± 0.318 kg m–2, respectively. The difference between the body mass indices of the two groups was statistically significant (P < 0.01, Mann–Whitney U-test), suggesting that the animals fed with a high-fat diet may be overweight. Light microscopic investigation showed a dilatation in blood vessels and Bowman’s space, mononuclear cell infiltration, degeneration in nephrons, including glomerulosclerosis and tubular defects, and an increase in the connective tissue in the kidneys in the experimental group. Conclusion: We concluded that High-fat diets have a profound influence on renal structure and morphometry thus increasing the susceptibility of the kidneys to damage.